A Values-Based Framework for Community Food Choices. (1st February 2010) - Gregory, Nicole; Gregory, Robin
Abstract : This paper examines the definition and implementation of community-based alternative food systems (AFS), drawing on examples from British Columbia, Canada. We seek to reframe the goals of AFS by focusing on the values associated with food production, distribution and consumption strategies. We argue that current AFS thinking suffers from an over reliance on policies reflecting single rather than multiple objectives and arguments over specific alternatives rather than a values-focused debate. A decision-focused approach, using a consequence matrix, is proposed to link people's expressed values to food policy responses and clarify trade-offs across options. This reframing should encourage new dialogue, new policy alternatives, and increased acceptance of actions supporting AFS.